A highly-flexible cyclic-decavanadate ligand for interconversion of dinuclear- and trinuclear-cobalt(ii) and manganese(ii) cores. Issue 60 (1st August 2017) - Maruyama, Tatsuya; Kikukawa, Yuji; Sakiyama, Hiroshi; Katayama, Misaki; Inada, Yasuhiro; Hayashi, Yoshihito
Abstract : The conformation of a cyclic-decavanadate ligand was reversibly transformed in response to the nuclearity of the central metal core. Abstract : The structure transformation of multinuclear-metal-cores can change catalytic, optical, and magnetic properties. Cyclic decavanadate ligands exhibit versatility in the number and the direction of the coordination sites by changing the conformation to stabilize various multinuclear-metal-cores, while organic multinucleating ligands require specific design for each of the multimetal complexes due to their structure directing ability. The flexibility of cyclic decavanadate ligands is demonstrated here to achieve accommodation of dinuclear or trinuclear units by using the same ligand. The reaction of a dinuclear-cobalt-core-containing decavanadate [Co2 (H2 O)2 V10 O30 ] 6− (Co2 ) with 1 equiv. of Co(OAc)2 (OAc = acetate) gave a trinuclear-cobalt-core-containing decavanadate [Co3 (H2 O)(OAc)V10 O30 ] 5− (Co3 ) in high yield. The central cobalt core exhibited an incomplete-cubane-type structure. The decavanadate ring contracts to accommodate a smaller dinuclear unit by taking a wavy conformation and expands to accommodate the larger trinuclear unit. The reverse reaction quantitatively proceeded by the addition of 5 equiv. of [VO3 ] − with respect toCo3 . Although a trinuclear-manganese-core-containing decavanadate [Mn3 (H2 O)(OAc)V10 O30 ] 5− (Mn3 ) possesses the same structure as that ofCo3, the addition of 5 equiv. of [VO3 ] − yielded a different structure of a dinuclear-manganese-core-containing decavanadate [Mn2 V10 O30 ] 6− (Mn2 ) with two cyclic pentavanadate ligands sandwiching the manganese core. Thus, the conformations of the cyclic decavanadates are rearranged to respond to the central metal core structures. EXAFS study suggests both manganese complexes maintain the molecular structure in solution. The simultaneous analyses of the magnetic susceptibility data and the magnetization data revealed the switch of magnetic interaction modes from ferromagnetic in dinuclear complexes to mixed ferromagnetic and antiferromagnetic interactions in trinuclear complexes: the ferromagnetic interaction in dinuclear units ofCo2 ( J = 8.05 cm −1 ) andMn2 ( J = 0.76 cm −1 ) ( H ex = − JS 1 S 2 ), and the ferromagnetic and antiferromagnetic interactions inCo3 ( J = −1.59 cm −1 and J ′ = 13.6 cm −1 ) andMn3 ( J = −2.20 cm −1 and J ′ = 0.07 cm −1 ) ( H ex = − JS A1 S A2 − J ′[ S A1 S B + S A2 S B ]) were studied.